1982
DOI: 10.1007/bf01136247
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of different wheat gliadins in coeliac disease

Abstract: To determine the toxic effect of different gliadins on coeliac patients, which has been variably assessed in the literature, wheat prolamines (gliadin) were separated into the main fractions alpha-, beta-, gamma-, and omega-gliadins by chromatography on Sulfopropyl Sephadex C-50. The chemical compositions of the gliands were characterized by polyacrylamide gel electrophoresis, amino-acid analysis, determination of amide nitrogen and peptide maps. The peptide fractions B2 and B3 were isolated from the gliadins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…First, since there is genetic variability between c~-gliadins (16)(17)(18), these findings do not allow us to definitively exclude that the T cells actually recognize peptides from this region. Second, although diseaserelevant epitopes can be found in the NH2-terminal region of ol-gliadin (39,40), other regions in both cx-gliadin (39,41) and other gliadins have been suggested to be implicated in the disease (38,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…First, since there is genetic variability between c~-gliadins (16)(17)(18), these findings do not allow us to definitively exclude that the T cells actually recognize peptides from this region. Second, although diseaserelevant epitopes can be found in the NH2-terminal region of ol-gliadin (39,40), other regions in both cx-gliadin (39,41) and other gliadins have been suggested to be implicated in the disease (38,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Bread wheat 0 a-Gliadin [69] 0 A-gliadin [73] 0 Tryptic a-gliadin digest [74] 0 Peptic-tryptic gluten digest [66,69,71,72] 0 Peptic-tryptic gliadin digest [33, 75 -78] 0 Peptic-tryptic-cotazym gliadin digest [33, 74, 78 -80] 0 Peptic-tryptic a-gliadin digest [33,41,66,75,76] 0 Peptic-tryptic b-gliadin digest [33,41,75,76] 0 Peptic-tryptic c-gliadin digest [33,41,75,76] 0 Peptic-tryptic x-gliadin digest [33,41,75,76] 0 Peptide 2R derived from a peptic-tryptic-cotazym digest of gliadin [81] 0 Peptides fractionated from a peptic-tryptic-cotazym digest including peptide fractions B 2 and B 3142 [40,41]. Peptide B 3142 is homologous to A-gliadin amino acid sequence 3 -55 [42] …”
Section: Toxic Cereal Fractionsmentioning
confidence: 99%
“…Synthetic peptides homologous to A-gliadin sequence 31 -43, 55 -55, and 56 -68 were infused directly into jejunum of treated coeliac patients and mucosal biopsies were tested for a number of immunological and biochemical parameters; peptides 31 -43 and 44 -55 were toxic, whereas the sequence 56 -68 was clearly inactive [43]. In some studies [40,41] an immunological test (leucocyte migration inhibition factor test) has also been used to investigate toxicity of several gliadin peptides in coeliac disease. In vivo studies have also been performed with rye whole flour and gluten as well as with barley whole flour; the results obtained clearly indicate the toxicity for coeliac patients of both rye and barley (Table 2).…”
Section: In Vivo Intolerance To Cereal Proteins and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the results of coeliac feeding trials with different wheat gliadin fractions (alpha, beta, gamma and omega) arc somewhat controversial [1], previous LMIF studies have indicated that alpha gliadin was the most coeliac-active [26,27], Also, work in our lab oratories indicated that alpha gliadin was the most ac tive fraction in the indirect LMIF [Devery et al, unpubl. data].…”
Section: Discussionmentioning
confidence: 99%